An analysis of factors influencing technical efficiency of health expenditures in China - Jingjing Cheng; Xianming Kuang; Ping Zhou; Weiran Sha (Health Economics Review)
Abstract China’s primary healthcare (PHC) system, together with rural healthcare services, remains the Achilles’ heel in the national healthcare system. Healthcare workers, specifically village doctors, are an integral part of the healthcare system. Using the two-stage data envelopment analysis (DEA) and Tobit regression analysis, this study aims to investigate the efficiency of healthcare expenditures on medical resources and services in China, as well as determine how different types of healthcare work influence efficiency. Compared with other types of healthcare workers, village doctors exerted a prominent impact on provincial and rural efficiency at all stages and played a key role in augmenting the efficiency of healthcare expenditures on health outcomes. Besides, township health centers (THCs) and village clinics (VCs) faced administrative overstaffing, mainly involving pharmacists, other nonmedical technologists, and health administrators, which adversely affected the efficiency of healthcare expenditures. This study suggests that the higher the proportion of these non-village doctor positions (e.g., pharmacists, health administrators, and nonmedical technologists) in THCs and VCs, the lower the efficiency of China’s PHC system. Overall, the priority should be enhancing the training and remuneration of village doctors and other healthcare workers in rural areas to further enhance their performance and increase the overall efficiency of China’s healthcare system.